Chapter ...in finibus Lucaniae. Historical cartography of the Tyrrhenian coast and demographic fluctuations - Pellettieri, Antonella (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The towns of Calabria Tortora, Aieta and Praia a mare with the Dino island and Fiuzzi gravitated towards Castrocucco and Maratea . Although divided by the Noce river they are in finibus Lucaniae they seem to belong to the same conformation as Castrocucco with vast coasts and beaches of very large dimensions. With the twentieth century and the mass tourism of the 60s, Aieta and Tortora begin a slow process of depopulation that leads to the birth of settlements towards the sea with Tortora marina and Praia a mare which had already become an autonomous municipality in 1928.